2014
DOI: 10.4162/nrp.2014.8.1.132
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis by a hexane extract of aged black garlic in the human leukemic U937 cells

Abstract: BACKGROUND/OBJECTIVES:In this study, the apoptogenic activity and mechanisms of cell death induced by hexane extract of aged black garlic (HEABG) were investigated in human leukemic U937 cells. MATERIALS/METHODS: Cytotoxicity was evaluated by MTT (3-(4, 5-dimethyl-thiazol-2-yl)-2, 5-diphenyl tetrazoliumbromide) assay. Apoptosis was detected using 4,6-diamidino-2-phenyllindile (DAPI) staining, agarose gel electrophoresis and flow cytometry. The protein levels were determined by Western blot analysis. Caspase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…BG exhibits excellent in vitro and in vivo therapeutic effects on several cancers (lung cancer, liver cancer, gastric cancer, leukemia, breast cancer, and colon cancer). A hexane extract of ABG was reported to exhibit anticancer effects in human leukemic U937 cells, as the extract induces caspase‐dependent apoptosis via an extrinsic pathway involving the death receptor 4 and Fas legend, while raising the ratio of Bax/Bcl‐2 protein expression via increasing the protein levels of pro‐apoptotic Bax and reducing the anti‐apoptotic Bcl‐2 expression (Park et al., ). ABG was found able to inhibit the growth of HT29 colon cancer cells and induce apoptosis via inhibiting the phosphatidylinositol 3‐kinase protein kinase B signaling pathway, because of the upregulation of phosphatase and tensin homology deleted on chromosome 10, downregulation of serine/threonine kinase and phosphorylated‐serine/threonine kinase expression, and suppression of the 70‐kDa ribosomal protein S6 kinase 1 at the mRNA and protein levels (Dong et al., ).…”
Section: Nutritional Value and Biological Activity Of Bgmentioning
confidence: 99%
“…BG exhibits excellent in vitro and in vivo therapeutic effects on several cancers (lung cancer, liver cancer, gastric cancer, leukemia, breast cancer, and colon cancer). A hexane extract of ABG was reported to exhibit anticancer effects in human leukemic U937 cells, as the extract induces caspase‐dependent apoptosis via an extrinsic pathway involving the death receptor 4 and Fas legend, while raising the ratio of Bax/Bcl‐2 protein expression via increasing the protein levels of pro‐apoptotic Bax and reducing the anti‐apoptotic Bcl‐2 expression (Park et al., ). ABG was found able to inhibit the growth of HT29 colon cancer cells and induce apoptosis via inhibiting the phosphatidylinositol 3‐kinase protein kinase B signaling pathway, because of the upregulation of phosphatase and tensin homology deleted on chromosome 10, downregulation of serine/threonine kinase and phosphorylated‐serine/threonine kinase expression, and suppression of the 70‐kDa ribosomal protein S6 kinase 1 at the mRNA and protein levels (Dong et al., ).…”
Section: Nutritional Value and Biological Activity Of Bgmentioning
confidence: 99%
“…That garlic organo-sulfur compounds test (5-100 µM) worked to protect against DNA damage (Belloir et al, 2006). Park et al, (2014) reported U937 cells were exposed to various concentrations of hexane extract aged black garlic (HEABG) for 24 h or 10 µg/mL of HEABG for the indicated times. The MTT assay was used to examine the effect of HEABG on cell viability.…”
Section: Activity Pharmacologymentioning
confidence: 99%
“…All filter discs had the same size, and any visual size differences are due to the various distances from which pictures were taken. H-NMR (400 MHz) and 13 C-NMR (101 MHz) spectra were recorded on a Bruker 400 NMR instrument with tetramethylsilane (TMS) as an internal standard. Only new compounds' NMR data is given.…”
Section: 4-disubstituted Quinazoline Derivatives Inhibits Angiogenementioning
confidence: 99%
“…56 (m, 4H), 2.41 (s, 6H), 1.97-1.85 (m, 2H), 1.05 (t, J = 7.1 Hz, 6H). 13 C-NMR (CDCl 3 ) δ = 171.05, 160.60, 159.10, 147.99, 141.19, 136.74, 132.56, 131.74, 127.35 -1-yl)propanemide (11d). Compound 8 was treated with excess N-methylpiperazine according to the general aminolysis procedure to afford 11d as a white solid in 44% yield after column chromatography with petroleum ether/EtOAc (10:1) elution; mp 167-168 °C.…”
Section: N-(2-(4-(3-(dimethylamino)propylamino)quinazolin-2-yl)phenylmentioning
confidence: 99%
See 1 more Smart Citation